Stakeholder Roles in the Rural Tourism Area Life Cycle of the Wisata Tani Betet, Nganjuk Regency - Nugroho, Bagus Satrio; Asmorowati, Sulikah (Jurnal Pariwisata Terapan, 2024)
The development of rural tourism in rural areas deserves attention due to its various advantage. In the Nganjuk Regency there is rural village destination which has received various awards, namely the Wisata Tani Betet. This study aims to describe the identification of stakeholders and the role of stakeholders in the development of Wisata Tani Betet. The research method is descriptive qualitative with data collection techniques of interviews using purposive techniques and supporting informants using snowball techniques, field observations and documentation studies. The theory used is based on stakeholder classification which includes primary, key and secondary stakeholders and stakeholder roles which includes policy creators, coordinators, facilitators, implementers and accelerator. In addition to describing the stakeholder role identified based on the Tourism Area Life Cycle (TALC) stages which is includes the exploration stage, the involvement stage, the development stage, the consolidation stage, the stagnation stage and the decline stage. The results show that Wisata Tani Betet has gone through 3 stages of the Tourism Area Life Cycle (TALC), which is the exploration stage, the involvement stage and the development stage. At each of these stages, stakeholders have carried out their respective roles, beside that local leadership and social capital owned by the Betet Village Government and Pokdarwis Regul, are factors that accelerate the development of tourism destinations. On the other hand, the lack of funding and the competencies of human resources is a barrier for tourism destinations to reach the next stage.